The CRACK programme: a scientific alliance for bridging healthcare research and public health policies in Italy - Giovanni Corrao; Giancarlo Cesana; Carlo La Vecchia; Giorgio Vittadini; Alberico Catapano; Giuseppe Mancia; Ovidio Brignoli; Alessandro Filippi; Luigi Cantarutti; Luca Merlino; Carlo Zocchetti; Flavia Carle (Epidemiology, Biostatistics and Public Health)
Healthcare utilisation databases, and other secondary data sources, have been used with growing frequency to assess health outcomes and healthcare interventions worldwide. Their increased popularity as a research tool is due to their timely availability, the large patient populations covered, low cost, and applicability for studying real-world clinical practice. Despite the need to measure Italian National Health Service performance both at regional and national levels, the wealth of good quality electronic data and the high standards of scientific research in this field, healthcare research and public health policies seem to progress along orthogonal dimensions in Italy. The main barriers to the development of evidence-based public health include the lack of understanding of evidence-based methodologies by policy makers, and of involvement of researchers in the policy process. The CRACK programme was launched by some academics from the Lombardy Region. By extensively using electronically stored data, epidemiologists, biostatisticians, pharmacologists and clinicians applied methods and evidence to several issues of healthcare research. The CRACK programme was based on their intention to remove barriers that thwart the process of bridging methods and findings from scientific journals to public health practice. This paper briefly describes aim, articulation and management of the CRACK programme, and discusses why it might find articulated application in Italy.